EFEKTIVITAS PENGGUNAAN MODEL PEMBELAJARAN TIPE NHT DALAM MENINGKATKAN PENGUASAAN MATERI DAN AKTIVITAS BELAJAR SISWA - Siska Meitasari; Tri Jalmo; Rini Rita T Marpaung (Jurnal Bioterdidik: Wahana Ekspresi Ilmiah, 2013)
Mastery of material is success rate in achievement destination and target. However the result of observation in class VIII of SMP Negeri 1 Baradatu, known that students learning outcomes is still low. This research has goal to know effectiveness  of the cooperative learning type numbered head together (nht) model to improve mastery of material and the activity of studying of the student.The design of this research is pretest-posttest non equivalent. The sample was students of class VIIID and VIIIE are selected by clusters of random sampling. The data of this research quantitative and qualitative data. Qualitative data got by average value pretest, posttest, and N-gain that analyzed statistically using uji t. Qualitative data is students learning activity, student response toward the use of NHT model that analyzed in descriptive. The result of research showed that effectiveness  of the cooperative learning type NHT to improve mastery get increasing with average value pretest (42,62); postes (80,21); dan N-gain (0,65). students activity all aspects observed in experiment class increasing that is asking aspect  (78,49%); response (79,57%); discussion (91,40%); giving opinion (76,88%), the high number supported by asking quality, response, and students opinion as the subject in growth and development in humans. In addition most of students gave positive response toward the use of  NHT model the data of question form (100%) students get excited and interested in NHT model and make students more active in discussing. Most of students (90,32%) student gave a positive response to toward the use of  NHT model. So, NHT model can  improve mastery of material and the activity of studying of the student.  Keywords: NHT model, mastery of material , activity of studying of the student, growth and development in humans.